Labor Markets and Poverty in Village Economies. Issue 2 (20th March 2017) - Bandiera, Oriana; Burgess, Robin; Das, Narayan; Gulesci, Selim; Rasul, Imran; Sulaiman, Munshi
Abstract: We study how women's choices over labor activities in village economies correlate with poverty and whether enabling the poorest women to take on the activities of their richer counterparts can set them on a sustainable trajectory out of poverty. To do this we conduct a large-scale randomized control trial, covering over 21, 000 households in 1, 309 villages surveyed four times over a seven-year period, to evaluate a nationwide program in Bangladesh that transfers livestock assets and skills to the poorest women. At baseline, the poorest women mostly engage in low return and seasonal casual wage labor while wealthier women solely engage in livestock rearing. The program enables poor women to start engaging in livestock rearing, increasing their aggregate labor supply and earnings. This leads to asset accumulation (livestock, land, and business assets) and poverty reduction, both sustained after four and seven years. These gains do not crowd out the livestock businesses of noneligible households while the wages these receive for casual jobs increase as the poor reduce their labor supply. Our results show that (i) the poor are able to take on the work activities of the nonpoor but face barriers to doing so, and, (ii) one-off interventions that remove these barriers lead to sustainable poverty reduction.